Active yet extremely durable Co3O4 spheroids of different texture without/with Au deposition for CO oxidation. Issue 2 (4th November 2014) - Yao, Y.; Su, Q.; Feng, X. Z.; Sun, B.; Ji, W. J.; Au, C. T.
Abstract : Co3 O4 spheroids of different texture without/with Au deposition were highly active yet very durable at 60–90 °C for CO oxidation. The calcined Co3 O4 -based catalysts and the yolk–shell type one were even more durable. The catalysts encountered obvious enhancement in CO oxidation activity via in situ pretreatment. Abstract : Spherically shaped Co3 O4 particles were synthesized by one-pot solvothermal treatment of Co(NO3 )2 in n -octanol that is free of structure-directing agents or pore formers. Au nanoparticles (2–4 nm) dispersed on the Co3 O4 substrates were fabricated using deposition–precipitation method. The as-synthesized Co3 O4 (without calcination) and the corresponding Au-containing catalyst achieved complete CO oxidation at 90 °C and 80 °C, respectively. Upon calcination, the condensed Co3 O4 formed on which uniform dispersion of small-sized flat Au entities (3.0 ± 0.6 nm) with large Au–Co3 O4 interfaces was established, showing complete CO oxidation at 110 °C. These two types of catalysts were found to be extremely durable even when operated in a period beyond 70 h under certain conditions. The calcined Co3 O4 -based Au catalyst can outperform Au/d-Co3 O4 in both activity and stability when subjected to a pre-reaction at 350 °C for 5 h. The yolk–shell type Co3 O4 @SiO2 catalysts synthesized by controllable acid-etching of Co3 O4 cores demonstrated an optimal Co3 O4 core–SiO2 shell interaction and a suitable Co3 O4 core particle size for CO oxidation. Both Co3 O4 substrates and Au/Co3 O4 systems were found to encounter substantial activity enhancement by in situ pretreatment. The pretreatment resulted in (i) transformation of AuO x to Au 0, (ii) higher fraction of surface Co 3+, and (iii) suitably lower concentration of surface oxygen adspecies, accounting for the enhanced activities.